European Medicines Agency extension of indication to include the combination immunotherapy cancer drug treatment with nivolumab (Opdivo) and ipilimumab (Yervoy) for adults with intermediate/poor-risk advanced renal cell carcinoma. Issue 6 (13th November 2020) - Ali, Sahra; Camarero, Jorge; Hennik, Paula van; Bolstad, Bjorg; Sommerfelt Grønvold, Maja; Syvertsen, Christian; Oddvar Strøm, Bjorn; Ökvist, Mats; Josephson, Filip; Keller-Stanislawski, Brigitte; Zafiropoulos, Nikolaos; Pean, Elias; et al.
Abstract : On the 15 November 2018, the Committee for Medicinal Products for Human Use adopted an extension to an existing indication for the use of nivolumab (Opdivo) in combination with ipilimumab (Yervoy) for the first-line treatment of adult patients with intermediate/poor-risk advanced renal cell carcinoma (RCC). The approval was based on results from the Pivotal CA209214 study, a randomised, open-label, phase III study, comparing nivolumab +ipilimumab with sunitinib in subjects≥18 years of age with previously untreated advanced RCC (not amenable for surgery or radiotherapy) or metastatic RCC, with a clear-cell component. A total of 1096 patients were randomised in the trial, of which 847 patients had intermediate/poor-risk RCC and received either nivolumab (n=425) in combination with ipilimumab administered every 3 weeks for 4 doses followed by nivolumab monotherapy 3 mg/kg every 2 weeks or sunitinib (n=422) administered orally for 4 weeks followed by 2 weeks off, every cycle. A statistically significant difference in overall survival (OS) was observed in the nivolumab + ipilimumab group compared with the sunitinib group in intermediate/poor-risk subjects (HR 0.63 (99.8% CI 0.44 to 0.89); stratified log-rank 2-sided p-value<0.0001). The median OS was not reached for the nivolumab + ipilimumab group and was 25.95 months for the sunitinib group. The OS rates were 89.5% and 86.2% at 6 months, and 80.1% and 72.1% at 12 months in the nivolumab +ipilimumab and the sunitinib groups, respectively. K-M curves separated after approximately 3 months, favouring nivolumab + ipilimumab. This was not mirrored in the favourable-risk patients where no statistically significant difference was observed between nivolumab + ipilimumab and sunitinib in favourable-risk patients (HR 1.45 (descriptive 99.8% CI 0.51 to 4.12), p =0.2715).